1995
DOI: 10.1038/376530a0
|View full text |Cite
|
Sign up to set email alerts
|

A human nucleoporin-like protein that specifically interacts with HIV Rev

Abstract: The Rev protein of human immunodeficiency virus type 1 (HIV-1) facilitates the nuclear export of unspliced and partly spliced viral RNAs. Rev contains an RNA binding domain, required for interaction with HIV-1 RNA, and an effector domain, required for RNA-bound Rev to function. The Rev effector domain is believed to interact with a cellular cofactor required for the Rev response and thus HIV-1 replication. Here we report the use of a yeast two-hybrid screen to clone human Rev interacting protein (hRIP), which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
213
1
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(222 citation statements)
references
References 19 publications
7
213
1
1
Order By: Relevance
“…This is consistent with our earlier results which demonstrated that the human immunode®ency type 1 (HIV-1) Rev/RRE regulatory axis could overcome the inhibitory e ect of the h1ARE . The HIV-1 Rev protein binds to its target RNA element in the nucleus and acts by promoting export of nuclear mRNAs (Emerman et al, 1989;Felber et al, 1989;HammarskjoÈ ld et al, 1989;Malim et al, 1989) through an alternative, productive route (Bogerd et al, 1995;Fisher et al, 1995;Fritz et al, 1995), thereby presumably preventing the h1ARE from interacting with nuclear proteins that mediate inhibition as the mRNA enters the cytoplasm. Recent reports have described the identi®cation of an RNaseE like activity in mammalian cells and have shown that partially puri®ed mammalian RNaseE cleaves AUUUA containing RNAs in vitro (Wennborg et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with our earlier results which demonstrated that the human immunode®ency type 1 (HIV-1) Rev/RRE regulatory axis could overcome the inhibitory e ect of the h1ARE . The HIV-1 Rev protein binds to its target RNA element in the nucleus and acts by promoting export of nuclear mRNAs (Emerman et al, 1989;Felber et al, 1989;HammarskjoÈ ld et al, 1989;Malim et al, 1989) through an alternative, productive route (Bogerd et al, 1995;Fisher et al, 1995;Fritz et al, 1995), thereby presumably preventing the h1ARE from interacting with nuclear proteins that mediate inhibition as the mRNA enters the cytoplasm. Recent reports have described the identi®cation of an RNaseE like activity in mammalian cells and have shown that partially puri®ed mammalian RNaseE cleaves AUUUA containing RNAs in vitro (Wennborg et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Additional effects of Rev are likely to occur at the level of facilitating viral RNA transport or translation. These transport effects could involve the specific interplay of other cellular factors, such as the nucleoporin-like Rab͞Rip proteins (49)(50)(51) or eIF 5A (52,53), with the leucine-rich activation domain of Rev (7), which functions as a nuclear export signal (54,55). Mutation of this leucine-rich domain results in the formation of potent dominant-negative inhibitors of Rev (56), which already have shown promise in early clinical trials (57).…”
Section: Discussionmentioning
confidence: 99%
“…The yeast Riplp (Stutz et al, 1995) and the mammalian Rab/hRIPl (Bogerd et al, 1995;Fritz et al, 1995) are candidates for a NES receptor that were isolated in independent two-hybrid screens. These proteins contain multiple FG amino acid repeats typical of NPC proteins (nucleoporins; Rout and Wente, 1994).…”
Section: Introductionmentioning
confidence: 99%